A Rare and Interesting Case of a Massive Secondary Spinal Chondrosarcoma and Review of the Literature - Anthony Adimonye (Case Reports in Orthopedics)
Chondrosarcoma, the second most common primary malignancy of the bone, is malignant cartilage forming tumour that very rarely involves the axial skeleton. It may arise as a primary bone tumour or as a secondary lesion from a preexisting benign cartilaginous neoplasm such as osteochondroma or enchondroma. A rare case of a massive secondary lumbar spine chondrosarcoma is presented. Management consisted of an initial posterior spinal stabilization and fusion and then a curative radical en bloc tumour resection. A review of the literature is also presented.